A concept of absolute continuity and its characterization in terms of convergence in variation. Issue 16 (3rd February 2016) - Angeloni, Laura; Vinti, Gianluca
Abstract : We study the notion of φ‐absolute continuity, providing several equivalent definitions, and we prove a characterization of the space of φ‐absolutely continuous functions in terms of convergence in variation for a family of Mellin integral operators in the multidimensional setting.